Photobiomodulation Therapy Using Infrared (808 nm) Low Level Laser Therapy Associated with Strength Training in Knee Osteoarthritis: A Randomized placebo-controlled clinical trial - Elias Guidini Lima, Geovane; Lopes-Martins, Rodrigo Alvaro Brandão; Souza Ferreira Magalhães, Daniel; Martins Bovareto, Ariane; Carmanini Teixeira, Laiana; Silva Teixeira Rocha, Mariane; Oliveira Martinho, Karina; Bjørn Stausholm, Martin; Sardinha Leonardo L. Martins, Patrícia; Farage Frade de Barros, Amanda; Cristina Nuñez, Silvia; Magnus Bjordal, Jan; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Mechanisms for significant clinical and statistical benefits of photobiomodulation (PBMT) in the treatment of knee osteoarthritis (KOA) include anti-inflammatory effects, optimization of tissue repair, improved muscle function and analgesia. The effectiveness of (PBMT) associated with strength training (ST), in the form of strength training, has been investigated in randomized clinical trials, but the results are not well clarified. The aim of this study was to evaluate the effects of ST associated with PBMT on joint pain intensity, range of motion, physical function and muscle strength of the quadriceps femoris and hamstrings in patients diagnosed with KOA. Twenty-eight adult patients of both genders with KOA were randomly distributed in 2 treatment groups, performed 3 times a week, for 6 weeks: ST Group (ST), submitted to stretching, self- mobilization, muscle strengthening and sensorimotor training and ST and STP Group (STP), submitted to the same program as the ST followed by infrared laser irradiation (Therapy XT, DMC, São Carlos, Brasil, l= 808 nm, P= 100mW, 5 points in the medial joint region and 4 points lateral, 3 J/point, 30 s/point). Blinded evaluators assessed pain at movent and no movement and range of motion using Analogic Visual Scale and goniometry, respectively. To assess physical function, the WOMAC questionnaire (Western Ontario and MacMaster University Osteoarthritis Index) and functional tests were used: Sit and stand test; 2 min-walk test. The muscular strength of the quadriceps and hamstrings were measured using an isometric dynamometer. The evaluations were performed in 4 moments: before (EV0), during (EV1: 3 weeks of treatment), at the end (EV2: after 6 weeks of treatment) and 30 days after the end of treatment (follow-up). The STP group showed a significant reduction in pain intensity at rest and at movement in EV1, as well as, significant improvement in relation to stiffness, total WOMAC and knee flexion amplitude, an improvement in physical function and an increase in muscle strength of quadriceps femoris when compared to ST group (p <0.05). In the assessment of the strength of the hamstring muscles, there was no significant difference between the groups at any time evaluated (p> 0.05). ST associated with PBMT had greater effects in reducing joint pain intensity, active knee flexion, physical function and muscle strength, especially in the quadriceps femoris, than strength training alone in patients with KOA.